Primary cesarean section in multigravidae: a case control study - S., Madhva Prasad; Chauhan, Anahita R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Primary Cesarean Section (CS) is defined as CS in a patient who has not had a prior CS. While primigravidae contribute to the bulk of those undergoing primary CS, multigravidae (with only prior vaginal delivery) can also contribute. The purpose of this article is to examine the contribution of the group of multigravidae (with only prior vaginal delivery) and how they differ from primigravidae. Methods: A review of records was conducted for one year period. The confinements which were first or second para (which had undergone CS in either index pregnancy or previous pregnancy) were divided into primipara: primary CS and second para: primary CS. Various parameters were compared between the primipara undergoing primary CS and multipara undergoing primary CS. Results: Out of 1154 births, the number of CS was 401. Primary CS in primiparas was 266 (66.3%) and primary CS in multipara (with only prior vaginal deliveries) was 61(15.2%). Booking status, baby weights and NICU admission rates did not different significantly. Preterm deliveries, higher number of prior abortions; malpresentations, deep transverse arrest, antepartum hemorrhage was more common among the multipara group and the difference was statistically significant (p value < 0.05). Conclusions: Multipara (with prior vaginal delivery only) definitely contribute to primary CS rate and cannot be neglected. The profile of patients and the indications of CS in multipara appear to differ from those in primipara.